موارد الأسماء النبوية: دراسة وصفية تحليلية: The Resources the Prophetic Names: An Analytical Descriptive Study - Moustapha Al Amin (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
الملخص هذا البحث محاولة للكشف عن الموارد التي أخذ منها العلماء الأسماء النبوية؛ وتكمن أهمية البحث في تعلقه بجانب الأسماء النبوية التي لا تؤخذ دون دليل شرعي، فهي ضمن النطاق العام للحديث النبوي، ويهدف البحث إلى التعريف بالأسماء النبوية، وتحديد المعايير التي يصح اعتمادها، والوقوف على مظان الخطأ فيها، وجمع الموارد الأسمائية عند المؤلفين في الأسماء النبوية، ومعرفة ترتيب هذه الموارد من حيث الصحة، وقد انتهجت فيه المنهج الوصفي والمنهج التحليلي ببيان الموارد ومراتبها وطرق اشتقاقها، والتثبت من صحة الموارد، وسبل تقويمها، وخلص البحث إلى أربعة معايير لاعتماد الأسماء النبوية، وهي: صحة المورد الأسمائي، وصحة الاشتقاق، وضبط النقل، وعدم إيهام النقص، وحصر الموارد الأسمائية في ثمانية موارد، وهي: النص القرآني الصريح، ولازم النص القرآني، والقراءات الشاذة، والحديث المقبول، والحديث المردود، والآثار الموقوفة والمقطوعة، والتوراة والإنجيل وسائر الكتب السابقة، والأشعار التي مدح أو رثي بها رسول الله صلى الله عليه وسلم، ثم رتب الموارد حسب قوتها وثبوتها على خمس رتب، وهي: الاسم العلم عليه صلى الله عليه وسلم، ثم ما كان مورده قرآنيًا صريحًا، ثم ما صح من القراءات الشاذة وما كان مورده حديثًا مقبولًا، ثم ما مُدح به صلى الله عليه وسلم في حضرته من الأشعار وما رثي به من أصحابه العارفين به، ثم ما ورد في الكتب السابقة من أسمائه وأوصافه مما اعتد به أهل هذا الشأن وقبلوه، وأوصى بالعناية بتحقيق المخطوط من كتب الأسماء النبوية، ومزيد البحث في الاستدلال للأسماء المعتبرة. Abstract This research is an attempt to reveal the resources from which scholars took the prophetic names; the importance of the research lies in its relation to the prophetic names that are not taken without legal evidence, since they are within the general scope of the prophetic hadith, the research aims to identify the prophetic names, determine the valid criteria to be adopted, identify the suspicions in their error, to collect the nominal resources of the authors in the prophetic names , knowledge of these resources order in terms of validity, I have adopted the descriptive analytical approach explaining the resources and their ranks and their derivational methods, verifying the resources' validity, ways of evaluating. The result of research has concluded with four criteria to verify the prophetic names which are including validity of names’ resources, validity of derivation, confirmation of narration, and to not indicate inappropriate meanings. Also, It limited the nominal resources in eight resources including the explicit Qur’anic text, related to Qur’anic text, anomalous Qur’anic recitation, accepted hadith, rejected hadith, mauquf and maqthu traditions, Bible and Gospel and previous books, and the poems that praised or lamented Prophet ﷺ. Moreover, the research arranged the resources according to their strength and reliability into five ranks which are proper names of prophet ﷺ, names mentioned explicitly in Qur’an, names mentioned in valid and confirmed anomalous Qur’anic recitation and accepted hadith, names mentioned in poems that praised or lamented Prophet ﷺ by his companions, and then names and descriptions that mentioned in previous books and commonly accepted by scholars in this filed. The research recommended the careful investigation of the manuscript in the books of the prophetic names, and further research into the inference of the considered names.